Motivace pracovníků v high-tech firmě - Šmedek, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Cílem bakalářské práce je analyzovat hodnoty vybraného souboru zaměstnanců high-tech firmy. Dílčími cíli jsou analýza motivačních preferencí a analýza přístupu zaměstnanců k organizaci. Analýzu byla provedena prostřednictvím dvou dotazníků, Hofsteda VSM 94 a dotazníku zjišťujícího motivační preference. Z analýz bylo zjištěno, že prostředí je poměrně stresující, pracovníci jsou velcí individualisté a převládá u nich dlouhodobá orientace. Za nejvhodnější benefity považují dovolenou, vzdělání a příspěvek na zdravotní péči. Práci, kterou zkoumaný soubor vykonává považují za dobře finančně ohodnocenou, a daná práce je baví. Mezi návrhy, díky kterým bude možné zvýšit efektivnost výkonu, kvalitu práce, lze navrhnout zvýšení doby dovolené, příspěvek na vzdělání a rozšíření týmové spolupráce na pracovišti.

The aim of my bachelor thesis is to analyze the values of the selected group of employees in high-tech company. The other partial aims were to analyze motivation preferences of employees and also analyze employee’s attitude towards the company. The analysis was based on two question-forms, Hofsteda VSM 94 and question-form asking about motivation preferences. I have found out from these analyses that the environment is quite stressful, employees are big individualists and long-term orientation is dominating there. The most valuable benefits for employees are: paid holiday, education and health care contribution. The work, this selected group was doing was rated as well paid and their work satisfies them. As a suggestion it could be recommended to offer more days of holiday, education contribution and expansion of team cooperation on their work place. This could help to the company to achieve increased efficiency of employee’s performance
The Motivation of Employees in High-tech Company
Keywords: Motivace; dotazník; zaměstnanci; vzdělání; high-tech firma; finanční ohodnocení; Motivation; questionnaire; staff; education; high-tech company; financial valuation